What's luck got to do with it? Commentary on Rowland and Spaniol (2021). Issue 1 (10th November 2021) - von der Gracht, Heiko A.
Abstract: This commentary refers to the retrospective review by Rowland and Spaniol in Futures and Foresight Science (2021), which provides interesting insights into Kees van der Heijden's character and work 25 years after his famous book Scenarios: The art of strategic conversation was first published. The commentator draws on his own personal experience of Kees' work and book, including a seminar with him at the University of Oxford in 2011, as well as applying the book's fundamentals in his own research and advisory work over the past ten years.